Chemical compounds and mechanisms involved in the formation and stabilization of foam in sparkling wines. Issue 13 (20th July 2019) - Kemp, Belinda; Condé, Bruna; Jégou, Sandrine; Howell, Kate; Vasserot, Yann; Marchal, Richard
ABSTRACT: The visual properties of sparkling wine including foam and bubbles are an indicator of sparkling wine quality. Foam properties, particularly foam height (FH) and foam stability (TS), are significantly influenced by the chemical composition of the wine. This review investigates our current knowledge of specific chemical compounds and, the mechanisms by which they influence the foam properties of sparkling wines. Grape and yeast proteins, amino acids, polysaccharides, phenolic compounds, organic acids, fatty acids, ethanol and sugar are examined with respect to their contribution to foam characteristics in sparkling wines made with the Traditional, Transfer, and Charmat and carbonation methods. Contradictory results have been identified that appear to be due to the analytical methods used to measure and quantify compounds and foam. Biopolymer complexes are discussed and absent knowledge with regards to thaumatin-like proteins (TLPs), polysaccharides, amino acids, oak-derived phenolic compounds and organic acids are identified. Future research is also likely to concentrate on visual analysis of sparkling wines by in-depth imaging analysis and specific sensory analysis techniques.